An Approach to Assessment of Video Game-based Learning using Structural Equation Model - Bolívar Barón, Holman; Castillo Salinas, Sandra; González-Crespo, Rubén (Proceedings of the 2014 9TH iberian conference on information systems and technologies (CISTI 2014), 2020)
Instructional activities should allow applying the knowledge acquired in the day by day and in real situations. Different studies evidence the potential impact of video games on learning, however very few empirical studies that focus on continuous assessment. On the other hand, because the variables that influence the achievement of learning objectives are different levels becomes complex to validation the effectiveness of an assessment of game-based learning, therefore, it is necessary to test inferences on academic development, testing hypotheses rigorous causal. We propose the use of multivariate analysis based on structural equation modeling as it facilitates the establishment of dependency relationships, to validate the proposal; we have performed an empirical test analytical applying a sequence of scenarios different to stimulate cognitive function of planning in a child population.
Keywords: multivariate analysis; structural equation modeling; cognitive training; game-based assessment; game-based learning; WOS(2); Scopus(2)